Design of a nanoscale gold-coated photonic crystal fiber biosensor - Sarker, Sanchita; Vigneswaran, Dhasarathan; Studnička, Filip (Frontiers in Physics, 2023)
A simple two-layer refractive index sensor based on the surface plasmon resonance has been proposed in this work which shows high sensitivity for detecting unknown analytes. Hexagonal and octagonal shaped air hole rings have been introduced in the first and second layer in this design respectively. This gold coated plasmonic sensing scheme provides the broad sensing limit of analyte 1.32-1.40. The sensing performance has been examined applying the finite element method. The wavelength interrogation method has demonstrated a maximal wavelength sensitivity of 9000 nm/RIU (Refractive Index Unit). The maximal amplitude sensitivity of 1902 RIU-1 has been exhibited in y-polarized mode using the amplitude interrogation method. Moreover, the maximal sensor resolution of 1.11 × 10−5 RIU covers the entire sensing range. Furthermore, by adjusting the air hole diameter, pitch, and depth of the gold layer coating, many more investigations have been demonstrated in this design. This highly sensitive sensor is very convincing to be used in many applications like chemical, biological and also in physical sensing analysis